Analysis of nAChR Autoantibodies Against Extracellular Epitopes in MG Patients - Michail, Maria; Zouvelou, Vasiliki; Belimezi, Maria; Haroniti, Anna; Zouridakis, Marios; Zisimopoulou, Paraskevi (Frontiers in Neurology, 2022)
Myasthenia gravis (MG) is an autoimmune disorder caused by autoantibodies targeting components of the postsynaptic membrane of the neuromuscular junction (NMJ), leading to neuromuscular transmission deficiency. In the vast majority of patients, these autoantibodies target the nicotinic acetylcholine receptor (nAChR), a heteropentameric ion channel anchored to the postsynaptic membrane of the NMJ. MG patients’ autoantibodies may target all the subunits of the receptor at both their extracellular and intracellular regions. Here, we combine immunoadsorption with a cell-based assay to examine the specificity of the patients’ autoantibodies against the extracellular part of the nAChR. Our results reveal that these autoantibodies can be divided into distinct groups, based on their target, with probably different impact on disease severity. Although our findings are based on a small sample group of patients, they strongly support that additional analysis of the specificity of the autoantibodies of MG patients could serve as a valuable tool for the clinicians’ decision on the treatment strategy to be followed.